Математичні моделі керування процесами фінансування інвестиційних проектів - Moskalenko, V. V.; Kondrashchenko, V. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2011)
The construction of an optimal scheme of financing of the investment project with the involvement of external sources of financing are considered. A complex of mathematical models, relevant to the specific forms of financing each of which allows to calculate the optimal financing scheme and get an estimate of its cost-effectiveness taking into account the characteristics of each specific forms is proposed.